Generalized microbundles and locally flat imbeddings - Matuzevičius, A. (Lithuanian Mathematical Journal, 1971)
The abstracts (in two languages) can be found in the pdf file of the article. Original author name(s) and title in Russian and Lithuanian: А. И. Матузявичюс. Обобщенные микропучки и локально плоские вложения A. Matuzevičius. Apibendrinti mikroišluoksniavimai ir lokaliai plokšti įdėjimai